2021
DOI: 10.1115/1.4051551
|View full text |Cite
|
Sign up to set email alerts
|

Analytical and Numerical Simulation of Asymmetric Converging Flow of Gas Under Drill Bits in Reverse Circulation Gas Drilling

Abstract: Reverse circulation gas drilling has been considered to solve engineering problems such as formation water influx, wellbore instability, and excess gas requirement in gas drilling. The performance of reverse circulation gas drilling depends to a large extent on the structure design of drill bit. An analytical model and a numerical model were developed in this study to simulate the asymmetric converging flow of gas under drill bit for reverse circulation gas drilling. The two models were compared and applied to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Due to unpredictable formation conditions, time-varying stress state of drilling tools, irregular borehole bottom, and wear of drill bit, simplification is introduced when drill bit simulation model is built. Firstly, since linear velocity of a drill bit is much smaller than flow velocities of the drilling fluid, drill bit rotation is not considered when constructing the model to study the flow field characteristics [21,22]. Secondly, in order to decrease the calculation time and enhance the convergence rate, the fillets, chamfers and other structures that do not affect the calculation results, are ignored.…”
Section: Fluid Domain and Meshingmentioning
confidence: 99%
“…Due to unpredictable formation conditions, time-varying stress state of drilling tools, irregular borehole bottom, and wear of drill bit, simplification is introduced when drill bit simulation model is built. Firstly, since linear velocity of a drill bit is much smaller than flow velocities of the drilling fluid, drill bit rotation is not considered when constructing the model to study the flow field characteristics [21,22]. Secondly, in order to decrease the calculation time and enhance the convergence rate, the fillets, chamfers and other structures that do not affect the calculation results, are ignored.…”
Section: Fluid Domain and Meshingmentioning
confidence: 99%
“…Han et al 14,15 found that a reasonable air velocity was conducive to discharge coal cuttings in the study of coal seam RC. Finally, Yang et al 16 studied the effect of bit structure on RC drilling performance.…”
Section: Introductionmentioning
confidence: 99%
“…DTH hammer RC drilling is an innovative percussive-rotary drilling technology driven by compressed air and is a potentially effective technology for large-diameter wells [13]. It is a fast and cost-effective way to reduce the air injection rate by at least 70% and improve hole cleaning efficiency [14]. In air RC drilling, compressed air enters the annulus of the dual-wall drill pipe through a dualwall swivel.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies show that the RC drill bit is the key component to forming air reverse circulation. Most previous work on RC drilling focused on the structural design of drill bits that control cutting transport at the bottom hole [14][15][16][17]. The range of diameters of these RC drill bits studied in previous work was from 80 to 600 mm.…”
Section: Introductionmentioning
confidence: 99%